Hate Speech on Students of Al Muhajirin Boarding Schoolkutai Kartanegara - Gunawan, Muhammad Henry; Zainuddin, Muhammad (ASIAN PUBLISHER, 2023)
The purpose of this study is to describe hate speech in the speech of students of the Al Muhajirin Islamic boarding school. While language is essential for communication between speakers, a person uses polite, polite words and sometimes uses words in the form of swear words. This study's object of observation was the participants' speech at Al Muhajirin Islamic Boarding School. In this study, researchers used a qualitative description approach with conversational listening techniques using Dell Hymes's 1972 SPEAKING theory (Setting/Sense, Participants, Ends, Act sequence, Key, Instrumentalities, Norms, Genres). From the results of this study, we can conclude what participants often use hateful words and what meanings are contained in these hateful words. With this, positive and negative tendencies will be seen and can be assessed in participants' speech in their daily lives.